(Not) Home alone: Antigen presenting cell – T Cell communication in barrier tissues - Neuwirth, Teresa; Knapp, Katja; Stary, Georg (Frontiers in Immunology, 2022)
Priming of T cells by antigen presenting cells (APCs) is essential for T cell fate decisions, enabling T cells to migrate to specific tissues to exert their effector functions. Previously, these interactions were mainly explored using blood-derived cells or animal models. With great advances in single cell RNA-sequencing techniques enabling analysis of tissue-derived cells, it has become clear that subsets of APCs are responsible for priming and modulating heterogeneous T cell effector responses in different tissues. This composition of APCs and T cells in tissues is essential for maintaining homeostasis and is known to be skewed in infection and inflammation, leading to pathological T cell responses. This review highlights the commonalities and differences of T cell priming and subsequent effector function in multiple barrier tissues such as the skin, intestine and female reproductive tract. Further, we provide an overview of how this process is altered during tissue-specific infections which are known to cause chronic inflammation and how this knowledge could be harnessed to modify T cell responses in barrier tissue.